Usos de las TIC en América Latina: Una caracterización (2017)
The information communication technologies - ICT generated a productive, economic and social dynamism through developed countries for the last four decades, with the digital technological and industrial revolution. These facts, transformed the process of innovation, production and global markets. Phenomenon observed in the macro and micro contexts. The aim of this document was a statistical analysis that shows tendencies in the use of ICT in Latin America in three different periods during the first decade of the twentieth century. The methodology used was ANOVA with simple variance and statistical average with test F. At same time, the factorials and clusters were the techniques handled in cross-sectional studies with variable proxies; it was a sample for twenty-two countries, out of thirty-three. The results showed the actual behavior of ICT in different clusters, highlighting potential economic synergies among the countries studied. The work was completed showing that in Latin America the use and application of ICT is still marginal for most countries, these evidences were contrasted with previous studies and current international literature on the macro and microstructures of developed countries. © 2017, Universidad de Tarapaca. All rights reserved.